Minha riqueza é fruto do meu trabalho: negros de cabedais no Sertão do Acaraú (1709-1822) - Souza, Raimundo Nonato Rodrigues de (2015)
The present study analyzes the presence of black families, Browns, and men of monetary assets in the process of occupation of the sertão do Acaraú, the formation of the country society whose settlement was inserted within a logical expansion of the agricultural frontier merchant. In this colonial society, various sesmeiros people with "mechanical defect" and of color, such as members of the family rabbit and Dias de Carvalho became Lords of uppers for mercy and blacks as José Monteiro de Melo, whose wealth was the result of his work. We also discussed about the black color in the backcountry, as were organized and sorted. Their experiences have enabled us thinking on family formation, increased kin, stability, important mechanism of family mobility in several alliances built by kinship or ritual. We seek to examine the social and economic mobility of black slaves, Freedmen and free; about the various strategies used by captives to their alforrias and about the relationships that these forged liners to survive as working poor free as well, regarding the relationship between slaves, Freedmen and owners, involving conflicts and negotiations.